2020
DOI: 10.1016/j.bioorg.2020.104246
|View full text |Cite
|
Sign up to set email alerts
|

The oxygenated products of cryptotanshinone by biotransformation with Cunninghamella elegans exerting anti-neuroinflammatory effects by inhibiting TLR 4-mediated MAPK signaling pathway

Abstract: Background: Neuroin ammatory processes are critical in the development and progression of Alzheimer's disease (AD). The potent anti-neuroin ammatory inhibitors are expected as the candidates to treat AD. Cryptotanshinone (1), a major bioactive constituent in the traditional Chinese medicinal herb Dan-Shen Salvia miltiorrhiza Bunge, has been reported to possess remarkable pharmacological activities, especially anti-oxidation and anti-in ammation. Methods: Cryptotanshinone (1) was biotransformed with the fungus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…These results indicate that CPT can promote the transformation of microglia/macrophages from the M1- to the M2-type and thus exerts neuroprotective effects. Researches have reported that CPT can inhibit neuroinflammation and improve cognitive dysfunction by acting on the NF-κB signaling pathway [ 56 , 57 ]. Therefore, we speculated that CPT may inhibit neuroinflammation and exert neuroprotective effects by inhibiting the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that CPT can promote the transformation of microglia/macrophages from the M1- to the M2-type and thus exerts neuroprotective effects. Researches have reported that CPT can inhibit neuroinflammation and improve cognitive dysfunction by acting on the NF-κB signaling pathway [ 56 , 57 ]. Therefore, we speculated that CPT may inhibit neuroinflammation and exert neuroprotective effects by inhibiting the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For one thing, bioactive compounds in TCM or TCM compound can reduce the synthetize of neurotoxic substances such as Aβ and Tau phosphorylation ( 31 ). For another thing, they can promote the clearance of toxic substances by increasing the toxic substance degradation enzyme, improving the blood-brain barrier function and promoting microglia phagocytosis ( 32 , 33 ). TCM also reduces neuronal apoptosis and loss of neurons caused by excessive autophagy ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the clinical trials of chemical drugs are summarized ( Table 1 ). CTS is being studied for a variety of pharmacological effects, including anti-inflammatory ( Wu et al, 2020 ; Liu et al, 2021a ), neuroprotective ( Mao et al, 2021 ), cardioprotective ( Wang et al, 2021e ), anti-fibrosis ( Lo et al, 2017 ; Zhang et al, 2020 ) and anti-tumor ( Dong et al, 2018 ; Han et al, 2019 ; Vundavilli et al, 2022 ). The diversity of pharmacological effects of CTS demonstrates unique potential for the treatment of high-incidence diseases.…”
Section: Introductionmentioning
confidence: 99%